Gender and Work Module 22 - Anderson, Erin (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This assignment provides you an opportunity to further explore a topic related to work and gender that we have addressed in the class or to investigate a topic we have not covered. As you research your chosen topic, think about how it contributes to our knowledge and understanding of the significance of gender in the world of work. You will share your research and findings with the class in a 10-15 minute presentation and submit a 10-15 page paper.Although biographical writing, popular media, and news stories may inform your decision to investigate a particular issue, your paper should be based on academic research andsources.